IDENTIFIKASI KERAGAMAN GENETIK ANTARA PELITA I/I DAN ROJOLELE MENGGUNAKAN MARKAH RAPD - Ishak, Ishak (Research Center for Biology-Indonesian Institute of Sciences, 2000)
The study of genomic diversity in molecular level on two sub-species i.e indica andjavanica rice types were represented by cv.Pelita 1/1 and Rojolele respectively.Javanica called padi bulu due to long aunt on the grain. Polymerase Chain Reaction (PCR)with 17 primers have been used for detecting genomic variation between these two sub-species.Results of experiment indicated that 12 out of 17 primers showed polymorphic DNA.This study would assist plant breeder to decide,whether to improve rice quality through crossing between javanica and indica is necessary.